Working with what you've got: unattractive males show greater mate-guarding effort in a duetting songbird. (January 2017) - Dowling, Jenélle; Webster, Michael S.
Abstract : When mates are limited, individuals should allocate resources to mating tactics that maximize fitness. In species with extra-pair paternity (EPP), males can invest in mate guarding, or, alternatively, in seeking EPP. Males should optimize fitness by adjusting investment according to their attractiveness to females, such that attractive males seek EPP, and unattractive males guard mates. This theory has received little empirical testing, leaving our understanding of the evolution of mating tactics incomplete; it is unclear how a male's relative attractiveness influences his tactics. We conducted observations and experiments on red-backed fairy-wrens ( Malurus melanocephalus ) to address this question. We found that older, more attractive (red–black) males sought EPP, whereas unattractive (brown) males invested in alternative tactics—physical and acoustic mate guarding. Younger red–black males used intermediate tactics. This suggests that males adopt mating tactics appropriate to their attributes. Males obtained similar reproductive success, suggesting these alternative tactics may maximize each male's paternity gain. Though it is likely that female choice also determines paternity, rather than just male tactics, we establish that the many interconnected components of a male's sexual phenotype influence the evolution of his decision-making rules, deepening our understanding of how mating tactics evolve under sexual selection.